I a una unitat lingüistica de l'occitan ? Enjòcs d'una definicion - Quentin Peyras (Lengas)
The both familiar and quite different aspect of the Occitan dialects can lead us to ask : "what makes the unity of this language?". Its current linguistic definition clearly explains its proximity to catalan, with which it forms an original subgroup of romance languages. But the features that specifically characterize the Occitan language are often not clearly presented. In this article we try to identify the features that make Occitan appear as a coherent and particular linguistic area, limiting ourself to phonetics and lexical aspects. We map these elements using data from all the linguistic atlases concerning the Occitan-speaking space and its surroundings. Establishing this knowledge about the unity and particularity of the Langue d'oc drives us to discuss our perception of this language and its variation, especially as actors in its revitalization.